Sistemas de fluxo contínuo e suas aplicações na síntese de IFAS - Ramos, Tiago de Oliveira (Universidade Federal de São Carlos, 2024)
Pharmaceuticals are present in our lives, whether in medicines for casual pains and allergies or for the treatment of serious health conditions. A country's autonomy about the production of pharmaceuticals is not only associated with cheaper production, it is also linked to that country's sovereignty, preventing the pharmaceutical market from being held hostage to external factors that could cause problems with the availability of medicines for the population. One of the ways we can think about investing in a new pharmaceutical industry is by improving processes with technologies that facilitate synthesis, such as continuous flow reaction technology, which has been applied in recent decades to the synthesis of organic molecules in the area of fine chemistry, such as the production of pharmaceutical ingredients. Over the last 25 years, continuous systems have been progressively gaining ground in the pharmaceutical industry for the synthesis of pharmaceutical ingredients, both on an industrial and laboratory scale. There is also the development of new synthetic routes adapted exclusively to continuous processes and/or the transposition of batch synthesis to flow synthesis. The application of this type of technology in the pharmaceutical industry brings several benefits to the production of active pharmaceutical ingredients, such as improved productivity, better use of energy, and reduced process costs, as well as increased safety in the process of synthesizing molecules with high value. These systems are made up of various units such as pumps, mixers, reactors, analyzers, separators, and purifiers which together form the so-called continuous flow synthesis setup. The smaller space occupied by flow systems compared to batch systems allows for simpler and safer operation, facilitating the development of synthetic routes for pharmaceutical ingredients. In this final paper (so-called TCC in Portuguese) we present some of the fundamental components of continuous flow systems used in the synthesis of molecules with biological activity, as well as show some syntheses published in the literature, such as the synthesis of fentanyl, as well as artemisinin.
Continuous flow systems and their applications in API synthesis
Keywords: Continuous flow; Organic synthesis; Active pharmaceutical ingredients; Fluxo contínuo; Síntese orgânica; Insumos farmacêuticos ativos; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA